Game of queens : the women who made sixteenth-century Europe - Gristwood, Sarah (New York : Basic Books, 2016)
"Sixteenth-century Europe saw an explosion of female rule. From Isabella of Castile and her granddaughter Mary Tudor, to Catherine de Medici, Anne Boleyn, and Elizabeth Tudor, women wielded enormous power over their territories for more than a hundred years. In the sixteenth century, as in our own, the phenomenon of the powerful woman offered challenges and opportunities. Opportunities, as when in 1529 Margaret of Austria and Louise of Savoy negotiated the "Ladies' peace" of Cambrai. Challenges, as when both Mary Queen of Scots and her kinswoman Elizabeth I came close to being destroyed by sexual scandal. A fascinating group biography of some of the most beloved (and reviled) queens in history, Game of Queens tells the story of the powerful women who drove European history"--
"Sixteenth-century Europe saw an explosion of female rule. Large swathes of the continent were under the firm hand of a dozen reigning women as queens, regents, mothers, wives, or counselors. From Isabella of Castile, her daughter Katherine of Aragon, and her granddaughter Mary Tudor, to Catherine de Medici, Anne Boleyn, and Elizabeth Tudor; from England and France to the Netherlands, and across the Holy Roman Empire, these women wielded enormous power over their territories, shaping the course of European history for over a century"--
Includes bibliographical references and index.
Keywords: Queens -- Europe -- History -- 16th century; Women heads of state -- Europe -- History -- 16th century; HISTORY / Modern / 16th Century; HISTORY / Europe / Western; BIOGRAPHY & AUTOBIOGRAPHY / Women; BIOGRAPHY & AUTOBIOGRAPHY / Royalty; Europe -- Politics and government -- 1492-1648.